Usage of E-Polytetrafluoroethylene (e-PTFE) Membrane for Managing Trabeculectomy Flap- Related Over-Filtration Due to Unavailability of Scleral Patch Graft during Nation-Wide Lockdown (Global Journal of Medical Research, 2021)
Scleral flap tears during trabeculectomy are difficult to repair in a predictable fashion. Donor scleral flap reinforcements are commonly preferred for managing trabeculectomy flaprelated over-filtration, leading to shallow anterior chamber (AC). Due to the advent of COVID-19 lockdown, especially in the initial phases, eye banking activities almost came to a standstill, with almost no corneal and/or scleral tissue retrievals. Hence, in this manuscript we have presented a mini case series with follow-up of two of our cases; where Gore-Tex (e-polytetrafluoroethylene) implant was used as an alternative to scleral patch graft, for managing trabeculectomy flaprelated over-filtration, with their pros and cons. Though Gore-Tex implant stability in both cases were contentious, it still served the purpose of managing the flap-related over-filtration and subsequent shallow AC.
Keywords: Gore-Tex; Trabeculectomy flap tear; COVID-19 lockdown; Shallow anterior chamber; Over-filtration